Legal Status Attributable to a Contract Party Displacing the Freedom to Agree - Drazdauskas, Stasys (Teisė, 2025)
In contract law, a return to the legal status as a tool for legal regulation of contractual legal relations has been observed since the end of the 19th century. Such legal regulation was of particular interest already in the 20th century to theorists who noted a decline of the importance of freedom of contract and studied the statuses of the consumer, the party acceding to the standard form contract, or the party with a greater market power. This article examines the trends in legal regulation over the past decades, revealing a wide variety of new statuses and classifying them according to the purposes of legal regulation. The main object of the research is EU legal sources, especially the new regulations in various areas related to the impact of contracts on wider public interests – in the areas of data protection, cyber security, financial sector, artificial intelligence, internet mediation services, and digital services. In addition to the doctrinal research methods (legal research criticism, theoretical reasoning, historical), analysis of research in other fields is used in search of an explanation for status-based regulation relying on the results of behavioural economics and neuroscience research. It is concluded that the assignment of various statuses to the parties to the contract can be justified by wider public interests, but the limits of such regulation should be sought, avoiding the creation of casuistic and inactive law.